PRODUKSI PEMBUATAN TOTEBAG TASKUSUKA DARI PENGOLAHAN LIMBAH KAIN BATIK - Febriana Mutia Isfianti; Maulidyah Indira Hasmarini (Universitas Muhammadiyah Surakarta, 2025)
Solo, a city in Central Java known for its Javanese culture and batik industry, generates a lot of patchwork waste from batik production. This waste is often not treated properly, causing environmental pollution. This research aims to process batik patchwork waste into totebag products that are economically valuable and environmentally friendly. A qualitative research method with a descriptive approach was used to document the totebag production process from patchwork waste. The process involved several stages, from collecting raw materials, making fabric patterns, to furing the totebag. The results show that totebag from batik patchwork waste not only reduce fabric waste but also have high economic and aesthetic value. The utilization of this waste encourages innovation in product design and increases the selling value and aesthetics of the products produced. The resulting TasKuSuka totebag product shows great potential in reducing fabric waste and having a positive impact on the local economy.